Antibiose relacionada a cultivo de Lactobacillus acidophilus. 1. Seleção de linhagem e estudo de meio de cultivo alternativo à base de soro de queijo - Pinto, Marcos Franke [UNESP]; Giglio Ponsano, Elisa Helena; Castro-Gomez, Raul Jórge Hernán [UNESP] (My University, 1996)
The production of antimicrobial compounds of some strains of Lactobacillus acidophilus has been studied. They have been grown in whey supplemented with soy milk. It has been found that the production of compounds is able to inhibit the growing of both target bacteria analysed: Staphylococcus aureus and Escherichia coli. The results showed a significant variation (p>0.05) depending on the strain of L. acidophilus and on the level of supplementation utilized. Most of the inhibition observed resulted from the presence of the lactic acid produced. It has also been found the production of other antimicrobial compounds showing inhibitory capacity. The action of these compounds was influenced by the substract pH.
Antibiosis associated to Lactobacillus acidophilus growth. 1. Strain selection and study of an alternative medium using whey
Keywords: Antibiosis; Fermentation; Lactobacillus acidophilus; Whey